Characterization of benthic biogeochemistry and ecology at three methane seep sites on the Northern U.S. Atlantic margin. (April 2018) - McVeigh, D.; Skarke, A.; Dekas, A.E.; Borrelli, C.; Hong, W.-L.; Marlow, J.J.; Pasulka, A.; Jungbluth, S.P.; Barco, R.A.; Djurhuus, A.
Abstract: Several hundred methane seeps were recently discovered along the U.S. Atlantic margin, a passive margin without a major hydrocarbon basin. These seeps represent a compelling opportunity to compare and contrast geochemical parameters, as well as the distribution and composition of associated chemosynthetic ecosystems, across geologically distinct seeps. Specifically, this study characterized the physical, chemical, geological, and biological features at Veatch Canyon, New England, and Shallop Canyon methane seep sites using a suite of state-of-the-art sampling and communication tools: AUV Sentry, HOV Alvin, a video-equipped multicore, and a real-time telepresence connection to the Inner Space Center (ISC) at the University of Rhode Island. Water column backscatter data collected by AUV Sentry confirmed previously detected gas emission and further indicated the presence of 13 actively emitting gas seeps within the Veatch Canyon survey area, 5 within the New England survey area, and 15 within the Shallop Canyon survey area. Complementary high-resolution seafloor bathymetry and backscatter mapping data indicated highly rugose morphology at all surveyed seep sites including the presence of extensive rock outcrops and bivalve beds. Video collected by HOV Alvin provided visual confirmation of gas plumes and the presence of chemosynthetic communities, including microbial mats and mussel beds, as well as large outcrops of authigenic carbonate rock surrounding locations of discrete gas emission. Bathymodiolus was the dominant species observed at the Veatch Canyon methane seep site, while the deep-sea red crab, Chaceon quinquedens, dominated the New England and Shallop Canyon seep sites. Elevated pore water sulfide concentrations suggested stimulation of sulfate-coupled anaerobic oxidation of methane (AOM) and/or degradation of organic matter in seep sediments relative to non-seep sediments; AOM was observed directly within overlying authigenic carbonate rocks. DNA sequencing of the surface sediments revealed diverse sulfide-oxidizing bacteria similar to the taxa described previously at other methane seeps, including members of the Thiotrichales and Campylobacterales . Together, these analyses provide one of the first interdisciplinary descriptions of sites within this massive seep system, setting the stage for more targeted, hypothesis-driven investigations. In this context, telepresence facilitated interdisciplinary research between specialists at the ISC and scientists and engineers at sea, enabling researchers to transfer data and maximize research efforts with sampling tools at sea. Our findings suggest that although the geological setting is distinct, the surficial microbial and macrofaunal communities closely resemble those of previously described methane seeps.